Current Immunotherapy Treatments of Primary Breast Cancer Subtypes - Savannah R. Brown; Emilie E. Vomhof-DeKrey (Biomedicines, 2024)
Breast cancer receives the most funding when compared to any other cancer type, according to a global study conducted by The Lancet. Nevertheless, this malignancy remains the most diagnosed cancer among women and relies heavily on a neoadjuvant treatment regimen of chemotherapy and targeted therapy. After standard treatment, 25–30% of breast cancer patients still develop disease recurrence and must undergo cytoreductive debulking surgery followed by intensive chemotherapy. An array of targeted therapies are currently being utilized and developed to alleviate negative side effects, eradicate cancer growth, and diminish disease recurrence. Immunotherapy is a promising cancer therapy that upregulates one’s immune system to stimulate a therapeutic effect and is utilized for cancer management among other ailments such as immunodeficiencies, hypersensitivity reactions, autoimmune diseases, inflammatory disorders, tissue and organ transplantation, and infectious diseases. This review highlights the five primary subtypes of breast cancer, provides a brief history of immunotherapy, evaluates the current landscape of treating breast cancer with immunotherapy, analyzes selected ongoing or recently completed immunotherapy clinical trials for hormone receptor-positive, HER2-enriched, and triple-negative breast cancer, and examines future trends for the treatment of breast cancer with immunotherapeutic techniques. This review provides a formal summary categorized by breast cancer subtype rather than types of immunotherapeutic treatment.